A MENTORING STRATEGY FOR UTILIZING TO THE NEED A SUCCESSION PLAN AS CAPITAL FOR THE DEVELOPMENT OF HUMAN RESOURCES FOR THE MILLENNIAL GENERATION - Khaeruman Khaeruman; Kristina Jalando-on Alubog; Hafidz Hanafiah (Yayasan Education and Social Center, 2023)
This research focuses on the challenges posed by the millennial generation's need for competent human resources in the corporate environment. Millennials possess distinctive attributes that differentiate them from preceding generations, necessitating companies to adopt a novel approach to harness this cohort's potential fully. The primary aim of this study is to examine the role of mentoring as a supportive mechanism in the context of succession planning. The objective of this initiative is anticipated to offer resolutions that cater to the requirements of the millennial workforce and align with the organisational needs. The present study was carried out utilising a qualitative case study design, employing an exploratory methodology. This methodology enables researchers to comprehend prevailing phenomena and investigate potential resolutions and inferences that can be derived. This study uses a triangulation technique, which collects data and information from various sources and situations. The findings of this research indicate that there are different mentoring models that businesses can use as part of a strategy to support succession planning. Businesses can implement these models. The management of companies' investments in their human resources can be improved by adopting a mentoring approach that considers employees' various ages as they progress through their careers. By taking advantage of this strategy, the process of employee regeneration will be able to function in a more effective and efficient manner.